Real-time parameter estimation of a MIMO system - (:unkn) unknown (INT ASSOC ENGINEERS-IAENG, 2008)
An experiment based method is proposed for parameter estimation of a class of linear multivariable systems. The method was applied to a pressure-level control process. Experimental time domain input/output data was utilized in a gray-box modeling approach. Continuous-time system transfer matrix parameters were estimated in real-time by the least-squares method. Simulation results of experimentally determined system transfer function matrix compare very well with the experimental results. The proposed method can be implemented conveniently on a desktop PC equipped with a data acquisition board for parameter estimation of moderately complex linear multivariable systems.
Keywords: least-squares method; MIMO systems; system identification; MULTIVARIABLE SYSTEMS; IDENTIFICATION